Finance and the economics of uncertainty - Demange, Gabrielle; Laroque, Guy. (Malden, MA : Blackwell Pub., 2006)
Presenting the basic principles and discussing them in a unified framework within elementary models, this text analyzes the allocation of risk in the context of the current literature, and emphasizes the role of information in decisions and prices.
Includes bibliographical references (p. 273-274) and index.
nmn 6/06/13
Loans
Keywords: Uncertainty; Finance -- Mathematical models